From antiferromagnetic and hidden order to Pauli paramagnetism in U M 2 Si 2 compounds with 5 f electron duality - Amorese, Andrea; Sundermann, Martin; Leedahl, Brett; Marino, Andrea; Takegami, Daisuke; Gretarsson, Hlynur; Gloskovskii, Andrei; Schlueter, Christoph; Haverkort, Maurits W.; Huang, Yingkai; Szlawska, Maria; Kaczorowski, Dariusz; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
The interplay of band-formation and electron-correlation effects in uranium heavy fermion compounds is the subject of an ongoing debate. Here unexpected insight has been gained from advanced spectroscopies on isostructural members of the U M 2 S i 2 family with different properties. The antiferromagnetic ( M = Pd,Ni), hidden order ( M = Ru), and Pauli-paramagnetic ( M = Fe) compounds all exhibit atomic-like U 5 f 2 multiplet states with singlet–singlet (quasi-doublet) symmetry while the U 5 f 3 weight increases from Pd → Ni → Ru → Fe, indicating increasing itineracy. This reveals the dual nature of the U-5 f electrons throughout the family; the local aspects persist in the hidden-order compound U R u 2 S i 2 and surprisingly even in the highly itinerant Pauli paramagnet U F e 2 S i 2 . This study gives guidelines for the theoretical treatment of U intermetallic systems. Using inelastic X-ray scattering beyond the dipole limit and hard X-ray photoelectron spectroscopy we establish the dual nature of the U 5 f electrons in U M 2 S i 2 ( M = Pd, Ni, Ru, Fe), regardless of their degree of delocalization. We have observed that the compounds have in common a local atomic-like state that is well described by the U 5 f 2 configuration with the Γ 1 ( 1 ) and Γ 2 quasi-doublet symmetry. The amount of the U 5 f 3 configuration, however, varies considerably across the U M 2 S i 2 series, indicating an increase of U 5 f itineracy in going from M = Pd to Ni to Ru and to the Fe compound. The identified electronic states explain the formation of the very large ordered magnetic moments in U P d 2 S i 2 and U N i 2 S i 2 , the availability of orbital degrees of freedom needed for the hidden order in U R u 2 S i 2 to occur, as well as the appearance of Pauli paramagnetism in U F e 2 S i 2 . A unified and systematic picture of the U M 2 S i 2 compounds may now be drawn, thereby providing suggestions for additional experiments to induce hidden order and/or superconductivity in U compounds with the tetragonal body-centered T h C r 2 S i 2 structure.